The Community Satisfaction of Transportation Facility Service: A Case of Bengkong Area, Batam - Daniel Arnoldi Gultom; Andri Irfan Rifai; Muhammad Isradi (Indonesian Journal of Multidisciplinary Science, 2022)
Bengkong is a densely populated area where most choose private vehicles over public transportation. This analysis aims to see the interests and performance of transportation users on the Bengkong road. High road use can affect road performance and traffic management, significantly affecting driving Comfort. The physical condition of the road must also be considered so that road users can drive well on the road. The results show that roads in Bengkong need to improve road conditions and the availability of public transport as this can affect travel effectiveness. Data showed an average interest of 3.46 and an average performance of 3.36, and the gap that was obtained was 0.05. Safety while driving holds the highest gap value, with a value of 2.00. While parking lot condition holds the lowest value at -0.54. The data shows that road conditions and driving safety should be improved in this area. At the same time, parking availability and road performance have good results and must maintain their performance.